The Plutocratic Bias in the CPI : Evidence from Spain - Ruiz Castillo, Javier (IMF Working Papers; Working Paper, 2000)
We define the plutocratic bias as the difference between inflation measured according to the current official CPI and a democratic index in which all households receive the same weight. We estimate that during the 1990s the plutocratic bias in Spain amounts to 0.055 percent per year. However, positive and negative biases cancel off when averaging over the whole period. The mean absolute bias is significantly larger, 0.090. We can explain most of the oscillations experimented by the plutocratic bias by the price behavior of three goods: a luxury good and two necessities.